P477 Prenatal screening and treatment of Chlamydia trachomatis infection to prevent adverse pregnancy outcomes – a pilot study. (14th July 2019) - Li, Changchang; Liu, Huihui; Nie, Juan; Qiu, Xiu; Wang, Cheng; Chen, Niannian; Fang, Dajun; Yang, Bin; Tang, Weiming
Abstract : Background: Chlamydia trachomatis (CT) infection is considered to be related to adverse pregnancy outcomes, but we are still not sure whether prenatal screening and treatment of CT infection can prevent these. We conducted a pilot study to investigate the feasibility and acceptability of prenatal CT screening and treatment in China, in order to collect preliminary data for a RCT. Methods: We recruited pregnant women at a gestational age between 12–14 weeks in a hospital in Guangzhou, China in April and May of 2018. All participants were screened for CT using Nucleic Acid Amplification Testing at the registry. Chlamydia-positive patients were provided one dose of azithromycin for treatment, and they were re-tested one-month after the treatment. We followed up every participant until delivery or end of pregnancy. We included nine adverse pregnancy outcomes (preterm birth (PTB), smaller than gestational age (SGA), birth defect, infant death, etc.). Results: Of 453 women reached, 306 agreed for the screening and provided urine samples for testing. 302 (98.7%) of the collected samples were valid for testing, and 283 (92.5%) of questionnaires were obtained, but one was withdrew before delivery. Finally, we included 282 participants in this analysis whose mean age was 30.46 year (SD: 3.88). 14(5%) women were CT-positive at the registry. Eleven cases received treatment and three refused. All treated women was re-tested as negative after treatment. In treatment group (N=11), neither adverse pregnancy outcomes nor side effect of treatment was observed. In the non-treatment group (N=3), one still birth was found. Among 268CT-negative pregnant women, we observed 13 PTBs, 20 SGAs and 1 heart birth defect. Conclusion: It is feasible and acceptable to conduct CT screening study among pregnant women. Although the sample size is limited, the study provided useful information for planning a RCT aimed to evaluate the efficacy of the testing and treatment strategy. Disclosure: No significant relationships.